Implementation of Continuous Integration and Continuous Deployment for Automated System Deployment - Bintang Rahmatullah; Moh. Idris (Komunitas Dosen Indonesia, 2025)
The increasing demand for software systems that are continuously updated requires deployment processes that are both automated and reliable. Manual deployment often causes delays, configuration inconsistencies, and downtime, especially in dynamic environments where changes occur frequently. To address these challenges, this study focuses on the implementation of a Continuous Integration and Continuous Deployment (CI/CD) pipeline that automates the entire build and release process for the KUPI System Information. The main objective of this research is to design and evaluate a self-hosted CI/CD architecture that integrates Docker, GitHub Actions, and Traefik to achieve a consistent, efficient, and secure deployment workflow. Unlike most previous studies that automate existing systems, this research applies CI/CD from the initial stage of system development, making automation a core architectural principle. The study employs an experimental method combined with iterative validation to test the performance, reliability, and resource utilization of the implemented pipeline. The results show that the automated pipeline successfully reduced the average deployment time to less than ten minutes, eliminated manual configuration errors, and maintained stable operation under continuous deployment cycles. Resource monitoring confirmed that CPU and memory consumption remained within optimal thresholds, ensuring system stability. In conclusion, this research demonstrates that implementing CI/CD from the early stages of system development can significantly enhance deployment speed, reliability, and operational consistency. This novelty provides a practical and reproducible model for small to medium-scale systems adopting DevOps practices with open-source tools while maintaining full control over infrastructure and security.